2018
DOI: 10.1097/pcc.0000000000001658
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Medication Burden in Pediatric Prolonged Critical Illness: A Potentially Modifiable Risk Factor for Delirium

Abstract: Objectives:It is important to describe and understand the prevalence and risk factors for the syndrome of delirium in critical illness. Since anticholinergic medication may contribute to the development of delirium in the PICU, we have sought to quantify anticholinergic medication exposure in patients with prolonged admission. We have used Anticholinergic Drug Scale scores to quantify the magnitude or extent of this burden.Design:Retrospective cohort study, January 2011 to December 2015.Setting:Single academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 26 publications
0
27
0
2
Order By: Relevance
“…25 Triggering factors include noise, lighting restriction during the day, absence of windows, opioids, propofol, steroids, and anticholinergic use. 21,26 Fragmentation, a reduced total sleep time, the absence of slow, deep sleep and REM sleep, as well as a displacement toward daytime hours, are alterations that may also act as triggers. Their presence worsens patient course, prolongs their stay, and increases the risk for complications and mortality.…”
Section: Sleep At the Intensive Care Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Triggering factors include noise, lighting restriction during the day, absence of windows, opioids, propofol, steroids, and anticholinergic use. 21,26 Fragmentation, a reduced total sleep time, the absence of slow, deep sleep and REM sleep, as well as a displacement toward daytime hours, are alterations that may also act as triggers. Their presence worsens patient course, prolongs their stay, and increases the risk for complications and mortality.…”
Section: Sleep At the Intensive Care Unitmentioning
confidence: 99%
“…In critically-ill patients, benzodiazepines are an independent risk factor for delirium. 26,33 The temporal relationship suggests causality and somehow supposes a contraindication to its use, although they are most commonly used as first-line drugs. 20,28,34 In adults, new agents, such as suvorexant (randomized, controlled study), would have a beneficial effect on the prevention of delirium.…”
Section: The Hospital Settingmentioning
confidence: 99%
“…El nivel de luz al aire libre es de, aproximadamente, 10 000 unidades lux (lux = un factores precipitantes el ruido, la iluminación restringida de día, la ausencia de ventanas, los opioides, el propofol y los esteroides, así como anticolinérgicos. 21,26 La fragmentación, el tiempo total del sueño disminuido, la ausencia del sueño lento profundo y del sueño REM, así como el desplazamiento hacia los horarios diurnos, constituyen alteraciones que pueden funcionar como desencadenantes. Su presencia agrava la evolución, prolonga la estadía y aumenta el riesgo de complicaciones y la mortalidad.…”
Section: El Medio Hospitalariounclassified
“…En los pacientes críticos, las benzodiazepinas son un factor independiente de riesgo para el desarrollo del delirium. 26,33 La relación temporal sugiere causalidad y, de alguna manera, supone una contraindicación a su uso, pese a ser las más utilizadas como drogas de primera línea. 20,28,34 En los adultos, nuevos agentes, como el suvorexant (estudio controlado aleatorizado), tendrían un efecto beneficioso en la prevención del delirium en los adultos.…”
Section: El Medio Hospitalariounclassified
“…17 In our previous work in the mechanically ventilated PICU population, we found that PICU patients undergoing prolonged mechanical ventilation received many medications with anticholinergic effects, with a median ADS score of 5 in that cohort. 18 Due to the possible mechanism of cholinergic blockade in SAE, the likely role of anticholinergic medications in PICU delirium, the purpose of this study was to measure the anticholinergic medication burden in these PICU patients with severe sepsis or septic shock. In addition, because of the sedation practices in the PICU, we sought to quantify the feasibility of delirium screening in this population.…”
Section: Introductionmentioning
confidence: 99%